Literacy strategies: a challenge that revolutionizes the boundaries of the school and language learning (Papeles, 2014)
This article is derived from a comparative case study in the District Educational Institution of Juana Escobar, in the fourth grade courses of Primary Education, in which a contrast between a socially homogeneous scenario was performed in relation to three levels of comparison: three control groups, an experimental group and an experimental subgroup. The process carried out in the research is constituted by a diagnosis, the implementation of reading and writing strategies in order to potentiate the development of communication skills and the analysis of three measurement instruments: an initial, an intermediate and a final test to determine the success or failure of the strategies used in the academic performance of students.
Keywords: Primary Education; communication skills; literacy; experimental group